Glucoregulatory Consequences and Cardiorespiratory Parameters in Rats Exposed to Chronic–Intermittent Hypoxia: Effects of the Duration of Exposure and Losartan - Fenik, Victor B.; Singletary, Tyana; Branconi, Jennifer L.; Davies, Richard O.; Kubin, Leszek (Frontiers in Neurology, 2012)
Background: Obstructive sleep apnea (OSA) is associated with glucose intolerance. Both chronic sleep disruption and recurrent blood oxygen desaturations (chronic-intermittent hypoxia – CIH) may cause, or exacerbate, metabolic derangements. Methods: To assess the impact of CIH alone, without accompanying upper airway obstructions, on the counter-regulatory response to glucose load and cardiorespiratory parameters, we exposed adult male Sprague-Dawley rats to CIH or sham room air exchanges for 10 h/day for 7, 21 or 35 days and then, one day after conclusion of CIH exposure, conducted intravenous glucose tolerance tests (ivgtt) under urethane anesthesia. Additional rats underwent 35 days of CIH followed by 35 days of regular housing, or had 35 day-long CIH exposure combined with daily administration of the type 1 angiotensin II receptor antagonist, losartan (15 mg/kg, p.o.), and then were also subjected to ivgtt. Results: Compared with the corresponding control groups, CIH rats had progressively reduced glucose-stimulated insulin release and impaired glucose clearance, only mildly elevated heart rate and/or arterial blood pressure and slightly reduced respiratory rate. The differences in insulin release between the CIH and sham-treated rats disappeared in the rats normally housed for 35 days after 35 days of CIH/sham exposure. The losartan-treated rats had improved insulin sensitivity, with no evidence of suppressed insulin release in the CIH group. Conclusions: In adult rats, the glucose-stimulated insulin release is gradually suppressed with the duration of exposure to CIH, but the effect is reversible. Elimination of the detrimental effect of CIH on insulin release by losartan suggests that CIH disrupts glucoregulation through angiotensin/catecholaminergic pathways. Accordingly, treatment with continuous positive airway pressure may ameliorate pre-diabetic conditions in OSA patients, in part, by reducing sympathoexcitatory effects of recurrent nocturnal hypoxia.